Nonencapsulated Neisseria meningitidis Strain Produces Amylopectin from Sucrose: Altering the Concept for Differentiation between N. meningitidis and N. polysaccharea - Zhu, Peixuan (American Society for Microbiology, 2003)
Neisseria meningitidis is the causative agent of meningococcal sepsis and meningitis. Neisseria polysaccharea is a nonpathogenic species. N. polysaccharea is able to use sucrose to produce amylopectin, a starch-like polysaccharide, which distinguishes it biochemically from the pathogenic species N. meningitidis. The data presented here indicate that this may be an insufficient criterion to distinguish between these two species. The nonencapsulated Neisseria strain 93246 expressed a phenotype of amylopectin production similar to that of N. polysaccharea. However, strain 93246 reacted with N. meningitidis serotype 4 and serosubtype P1.14 monoclonal antibodies and showed the N. meningitidis L1(8) lipo-oligosaccharide immunotype. Further analyses were performed on four genetic loci in strain 93246, and the results were compared with 7 N. meningitidis strains, 13 N. polysaccharea strains, and 2 N. gonorrhoeae strains. Three genetic loci, opcA, siaD, and lgt-1 in strain 93246, were the same as in N. meningitidis. Particularly, the siaD gene encoding polysialyltransferase responsible for biosynthesis of N. meningitidis group B capsule was detected in strain 93246. This siaD gene was inactivated by a frameshift mutation at the poly(C) tract, which makes strain 93246 identical to other nonencapsulated N. meningitidis strains. As expected, the ams gene encoding amylosucrase, responsible for production of amylopectin from sucrose, was detected in strain 93246 and all 13 N. polysaccharea strains but not in N. meningitidis and N. gonorrhoeae strains. These data suggest that strain 93246 is nonencapsulated N. meningitidis but has the ability to produce extracellular amylopectin from sucrose. The gene for amylopectin production in strain 93246 was likely imported from N. polysaccharea by horizontal genetic exchange. Therefore, we conclude that genetic analysis is required to complement the traditional phenotypic classification for the nonencapsulated Neisseria strains.